Reliable indoor power line communication systems: via application of advanced relaying processing - Wu, Xiaolin (Curtin University, 2015)
In this thesis, we focus on improving the performance of indoor power line communication (PLC) systems using relaying schemes. A method of modelling relay-involved PLC channels has been proposed. We study the optimal joint transceiver and relay power allocation problem for relay-assisted multicarrier indoor PLC systems. We transform the nonconvex problem into a group of sub-problems which can be efficiently solved using standard convex optimization techniques. The proposed schemes outperform conventional direct PLC systems.